2009
DOI: 10.2165/11317610-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Medication Use and Increased Risk of Falls in Hospitalized Elderly Patients

Abstract: Some drugs are associated with an increased risk of falls in the elderly and, when alternatives exist, should be avoided until cohort studies are conducted to confirm or refute these possible increased risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 17 publications
0
34
0
7
Order By: Relevance
“…A French retrospective case control study [26] reported that 50% of falls occurred in patients in their first week after hospital admission, with these classified as severe in 16% cases. The characteristics of the two groups under study (patients who fell and those who did not) were similar: there were no significant differences in variables such as age, sex, number of medicines or prevalence of hypertension or Parkinson's disease.…”
Section: Results With Discussionmentioning
confidence: 99%
“…A French retrospective case control study [26] reported that 50% of falls occurred in patients in their first week after hospital admission, with these classified as severe in 16% cases. The characteristics of the two groups under study (patients who fell and those who did not) were similar: there were no significant differences in variables such as age, sex, number of medicines or prevalence of hypertension or Parkinson's disease.…”
Section: Results With Discussionmentioning
confidence: 99%
“…8,16,17,[27][28][29][30][42][43][44][45][46][47][48] Medications including benzodiazepines, anticonvulsants, antihypertensives, antidepressants, and sleep aids have also been targeted as high-risk medications. 8,[26][27][28][31][32][33][34][35]42,[49][50][51][52][53][54][55][56] Two additional risk factors that are often mentioned are male sex and poor functioning or inability to independently perform activities of daily living. 13,15,19,24,27,35,56,57 …”
Section: Risk Stratificationmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Complications associated with falls among hospitalized patients can result in death, disability, increased hospital length of stay, placement in an extended care facility, psychological distress, and litigation. 1,4,[10][11][12][13] In addition, the cost of falls in the United States may be more than $40 billion by 2020.…”
mentioning
confidence: 99%
“…1,12,[18][19][20][21][22][23][26][27][28][29][30][31][32][33][34] Yet, falls continue to be a serious safety threat, especially for acutely ill, hospitalized patients. 2,[5][6][7][8]16,17,19,20,30,31 Nurses routinely assess hospitalized patients' risk for falls and educate patients on preventing falls. However, strategies to reduce falls have limited effectiveness if patients do not follow the fall-prevention plans.…”
mentioning
confidence: 99%